Kelimpahan Kodok Jam Pasir Leptophryne borbonica di Sepanjang Aliran Sungai Cisuren, Bodogol, Taman Nasional Gunung Gede Pangrango: Abundance of Hourglass Toad Leptophryne borbonica along Stream Gradient - Ardiansyah, Dhany; Karunia, Arini; Auliandina, Talita; Putri, Dien Anugerah; Noer, Mohamad Isnin (Bioma, 2014)
There is high spatial variation in physical and chemical characteristics both within and between streams, some of which has been linked to natural factors. Stream characteristics affect many biological and physical processes. Leptophryne borbonica is stream-dependent toad that spend their life completely in or around stream. The purpose of this study was to determine the effect of habitat characteristics on abundance of Leptophryne borbonica in Bodogol, Sukabumi, West Java. Survey was conducted to obtain data on 27 until 29 June 2013 along Cisuren stream of Bodogol. Parameters that used in this study were conductivity, temperature, humidity, and salinity. The findings showed that all physical factors of stream have weak correlation with the abundance of Leptophryne borbonica. Abiotic factors that forming an ecosystem could affect the abundance and distribution of a amphibians species, because amphibians are sensitive to environmental change. Our result suggested that chemical characteristics along this stream were within the range of fundamental niche of Leptophryne borbonica. However, the slightly different in the number of individuals obtained among plots indicated that there were other factors that may be at play.